Determinants of and sustainable practices to reduce food waste in UK restaurants from the case study of a UK buffet restaurant. - Vu, Thi Phuong Anh (2018)
This dissertation’s purpose aims at exploring the determinants of and sustainable practices to food waste in UK restaurants, especially buffet-style restaurants. Little past research has focused on food waste in the UK food service sector, particularly the restaurant industry. Qualitative content analysis with deductive approach has been utilised together with the help of Nvivo 12 software to process primary data collected through semi-structured interviews and observations conducted at a buffet restaurant in the UK. Through the reviewing process of literature, eight elements that might be the causes of food waste at restaurants together with the model to explain for the rationalisation and values behind customers’ behavior has been integrated to form a theoretical framework for the study. The core findings were the underlying reasons behind buffet restaurants’ operations and consumers’ behavior of wasting food and solutions to deal with the problem. Implications are provided for other types of restaurants in the UK as well.